Relation of neutrophil-to-lymphocyte and platelet-to-lymphocyte ratio with coronary artery disease severity in patients undergoing coronary angiography - (:unkn) unknown (POLSKIE TOWARZYSTOWO KARDIOLOGICZNE, 2015)
Background: Atherosclerosis is a chronic systemic inflammatory disease. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are systemic inflammatory markers that are correlated with poor cardiovascular outcomes. Aim: To explore the relation of NLR and PLR with severity of coronary artery disease (CAD). Methods: The study population consisted of 180 consecutive patients who underwent elective coronary angiography (CAG). While 100 patients (22 female, mean age: 60.6 +/- 12.6 years) had abnormal CAG, 80 patients (44 female, mean age: 57.2 +/- 10.9 years) had normal CAG. NLR and PLR were calculated as the ratio of neutrophil count to lymphocyte count and as the ratio of platelet count to lymphocyte count, respectively. Results: Although age distribution was similar between the two groups (p = 0.073), female gender was significantly higher in the normal CAG group (p < 0.001). Patients with abnormal CAG had significantly higher NLR and PLR when compared to patients with normal CAG (3.7 +/- 2.6 vs. 2.2 +/- 1.7, p < 0.001 and 125.9 +/- 72.3 vs. 102.6 +/- 33.8, p = 0.027, respectively). NLR and PLR were significantly correlated with SYNTAX score and GENSINI score. In logistic regression analyses, only NLR (odds ratio: 1.576, confidence interval: 1.198-2.072, p = 0.001) was an independent predictor of CAD. An NLR of 2.3 or higher predicted the CAD with a sensitivity of 66% and specificity of 70%. Conclusions: NLR and PLR seem to be a simple method to predict severity of CAD in patients undergoing elective CAG, and it may be part of cardiovascular examination before CAG.
Keywords: neutrophil-to-lymphocyte ratio; platelet-to-lymphocyte ratio; GENSINI; SYNTAX; coronary artery disease; ELEVATION MYOCARDIAL-INFARCTION; PLATELET/LYMPHOCYTE RATIO; ASSOCIATION; OUTCOMES; INFLAMMATION; UTILITY; RISK